The dopamine D1 receptor agonist SKF81297 has dose-related effects on locomotor activity but is without effect in a CER trace conditioning procedure conducted with two versus four trials - Pezze, Marie A.; Marshall, Hayley J.; Cassaday, Helen J. (Elsevier, 2016)
In an appetitively motivated procedure, we have previously reported that systemic treatment with the dopamine (DA) D1 receptor agonist SKF81297 (0.4 and 0.8 mg/kg) depressed acquisition at a 2s inter-stimulus-interval (ISI), suitable to detect trace conditioning impairment. However since DA is involved in reinforcement processes, the generality of effects across appetitively- and aversively-motivated trace conditioning procedures cannot be assumed. The present study tested the effects of SKF81297 (0.4 and 0.8 mg/kg) in an established conditioned emotional response (CER) procedure. Trace-dependent conditioning was clearly shown in two experiments: while conditioning was relatively strong at a 3-s ISI, it was attenuated at a 30-s ISI. This was shown after two (Experiment 1) or four (Experiment 2) conditioning trials conducted in - as far as possible - the same CER procedure. Contrary to prediction, in neither experiment was there any indication that trace conditioning was attenuated by treatment with 0.4 or 0.8 mg/kg SKF81297. In the same rats, locomotor activity was significantly enhanced at the 0.8 mg/kg dose of SKF81297. These results suggest that procedural details of the trace conditioning variant in use are an important determinant of the profile of dopaminergic modulation.